Disparities in the Prevalence of Unmet Needs and Their Consequences Among Black and White Older Adults. (October 2018) - Berridge, Clara; Mor, Vincent
Objective: We document differential prevalence of need for assistance with personal, instrumental, and mobility tasks and adverse consequences of unmet needs, nursing home relocation, and mortality among Black and White older adults.Method: Data are from the National Health and Aging Trends Study. Using logistic and multinomial logistic regression, we determine whether race is predictive of reporting need or adverse consequence and test the role of race as a moderator of the relationship between baseline need and three 1-year outcomes.Results: Black older adults are more likely to experience a consequence of unmet need (35.33% vs. 29.97%, p = .028) in unadjusted models. In adjusted models, we find no moderating effect of race on baseline need on nursing home placement (0.00, 95% confidence interval [CI] = [−2.43, 2.42], p = .991), mortality (0.73, 95% = [−1.58, 0.11], p = .089), or a Round 2 consequence of unmet (−0.51, 95% CI = [−1.15, 0.14], p = .121).Discussion: This work highlights the complex relationship between race, need, unmet need, mortality, and nursing home entry.